Oral Health and Nutritional Characteristics of Adults With Morbid Obesity: A Multivariate Analysis - Marquezin, Maria Carolina Salomé; Chaves-Júnior, Samuel de Carvalho; Rasera, Irineu; Pacheco, Elisane Rossin Pessotti; Gavião, Maria Beatriz Duarte; Lamy, Elsa; Castelo, Paula Midori (Frontiers in Nutrition, 2020)
The relationship between oral health and nutritional aspects are complex, especially in individuals with chronic diseases and comorbidities, such as morbid obesity. Thus, the aim of the present study was to identify oral health and nutritional-related patterns in 113 individuals, aged 19-68 years (92 females), seeking treatment for morbid obesity. Sociodemographic variables and medical records were examined, in addition to the consumption of fruit, vegetables, candies and processed foods. Measures of body mass index, neck, waist and hip, caries experience (DMFT index), Community Periodontal Index (CPI index), and salivary physicochemical aspects were gathered. Aspects of oral health-related quality of life and symptoms of dry mouth were evaluated by means of Oral Health Impact Profile (OHIP-14) and Xerostomia Inventory-XI questionnaires. K-means cluster analysis and, subsequently, comparisons between clusters (one-way ANOVA) were performed (=5%). Three clusters were generated: Cluster 1 (labeled ‘Young’; n=77) was characterized by younger participants with higher BMI, who reported the use of distractors while eating, the smallest number of meals/day, and who consumed sweetened drinks and processed food the day before. Cluster 2 (labeled ‘Diabetic individuals’; n=12) was characterized by older participants with the highest proportion of diabetic participants (100% were diabetic; 73% insulin users), lower BMI, higher DMFT index and OHIP-14 and xerostomia scores, and who reported having consumed fruit and vegetables the day before. Finally, Cluster 3 (labeled ‘Poor periodontal health’; n=24) was characterized by participants with the worse periodontal condition (higher CPI), and lower salivary flow, pH and buffer capacity. Cluster 1 and 2 were the groups that showed higher demand for nutritional and dietetic counseling, because of the poor eating behavior and higher serum glucose levels, respectively. On the other hand, Cluster 2 and 3 showed the higher demand for oral rehabilitation and dental treatment because of the loss of teeth and worse periodontal condition, respectively, besides the need for dietetic counseling. This sample of individuals with morbid obesity showed very unique oral-health and nutritional characteristics and special needs patterns that should be identified to adjust or change unhealthy habits, thus improving the assistance of this condition.